2023
DOI: 10.3390/plants12142731
|View full text |Cite
|
Sign up to set email alerts
|

SNAC3 Transcription Factor Enhances Arsenic Stress Tolerance and Grain Yield in Rice (Oryza sativa L.) through Regulating Physio-Biochemical Mechanisms, Stress-Responsive Genes, and Cryptochrome 1b

Abstract: Arsenic (As) is one of the toxic heavy metal pollutants found in the environment. An excess of As poses serious threats to plants and diminishes their growth and productivity. NAC transcription factors revealed a pivotal role in enhancing crops tolerance to different environmental stresses. The present study investigated, for the first time, the functional role of SNAC3 in boosting As stress tolerance and grain productivity in rice (Oryza sativa L.). Two SNAC3-overexpressing (SNAC3-OX) and two SNAC3-RNAi trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 79 publications
(133 reference statements)
0
4
0
Order By: Relevance
“…Similarly, the OsPRX38 auxin-catabolism-related gene, part of the class III peroxidases multigene family of plant-specific peroxidase, enhances As tolerance by activating stress-related mechanisms such as SOD (superoxide dismutase), PRX (peroxidase), GST (glutathione- s -transferase) activity promoting higher lignification in root cells, acting as a barrier to prevent the entry of As during As perception [ 77 ]. It has been reported that SNAC3 overexpression plays a pivotal role in boosting As stress tolerance and grain productivity in O. sativa by antioxidant enzymes, photosynthesis, and osmolyte accumulation [ 78 ].…”
Section: Mechanisms For Arsenic Perception and Signalingmentioning
confidence: 99%
“…Similarly, the OsPRX38 auxin-catabolism-related gene, part of the class III peroxidases multigene family of plant-specific peroxidase, enhances As tolerance by activating stress-related mechanisms such as SOD (superoxide dismutase), PRX (peroxidase), GST (glutathione- s -transferase) activity promoting higher lignification in root cells, acting as a barrier to prevent the entry of As during As perception [ 77 ]. It has been reported that SNAC3 overexpression plays a pivotal role in boosting As stress tolerance and grain productivity in O. sativa by antioxidant enzymes, photosynthesis, and osmolyte accumulation [ 78 ].…”
Section: Mechanisms For Arsenic Perception and Signalingmentioning
confidence: 99%
“…The overexpression of this gene significantly improved drought and salt tolerance in rice, with a 22–34% increase in yield compared to wild-type rice [ 106 ]. Similarly, the overexpression of the SNAC2 gene increased drought resistance in rice yields compared to wild-type rice yields [ 107 , 108 ]. Tran et al, cloned three Arabidopsis NAC family genes, ANAC019 , ANAC055 , and ANAC072 , and they discovered that the overexpression of these genes dramatically increased drought tolerance compared to the wild type, with ANAC072 being engaged in the ABA signaling system [ 109 ].…”
Section: Transcription Factors Involved In the Drought Stress Responsementioning
confidence: 99%
“…Data from ABA content, SNAC3 expression, and response in mutants suggest that SNAC3 may function mainly in an ABA-independent manner [96], in contrast to some previously reported NAC genes. Finally, last year, two SNAC3-OX lines and two SNAC3-RNAi lines were created and subjected to arsenic stress treatments [201]. Interestingly, SNAC3 overexpression significantly intensified rice tolerance to arsenic stress and boosted grain yield, while the expression elimination generated a contrary response in both parameters.…”
Section: The Relationship Of Aba and Et With Nacmentioning
confidence: 99%
“…Interestingly, SNAC3 overexpression significantly intensified rice tolerance to arsenic stress and boosted grain yield, while the expression elimination generated a contrary response in both parameters. For further clarification, SNAC3 overexpression induced the enzymatic antioxidant levels of transgenic rice lines which in turn scavenge ROS, causing decreased oxidative stress and enhanced arsenic stress tolerance [201].…”
Section: The Relationship Of Aba and Et With Nacmentioning
confidence: 99%